Supervision and Care Quality as Perceived by Redeployed Attendings, Fellows, and Residents During a COVID-19 Surge: Lessons for the Future. (23rd February 2022) - Young, John Q.; Friedman, Karen A.; Thakker, Krima; Hennus, Marije P.; Hennessy, Martina; Patterson, Aileen; Yacht, Andrew; ten Cate, Olle
Abstract : Purpose: To better prepare for potential future large-scale redeployments, this study examines quality of supervision and care as perceived by redeployed residents, fellows, and attendings during a COVID-19 surge. Method: During April and May 2020, attendings, fellows, and residents redeployed at 2 teaching hospitals were invited to participate in a survey, which included questions on respondents' prior experience; redeployed role; amount of supervision needed and received; and perceptions of quality of supervision, patient care, and interprofessional collaboration. Frequencies, means, and P values were calculated to compare perceptions by experience and trainee status. Narrative responses to 2 open-ended questions were independently coded; themes were constructed. Results: Overall, 152 of 297 (51.2%) individuals responded, including 64 of 142 attendings (45.1%), 40 of 79 fellows (50.6%), and 48 of 76 residents (63.2%). Fellows and attendings, regardless of prior experience, perceived supervision as adequate. In contrast, experienced residents reported receiving more supervision than needed, while inexperienced residents reported receiving less supervision than needed and rated overall supervision as poor. Attendings, fellows, and experienced residents rated the overall quality of care as acceptable to good, whereas inexperienced residents perceived overall quality of care as worse to much worse, particularly when compared with baseline. Conclusions: Narrative themes indicated that the quality of supervision and care was buffered by strong camaraderie, a culture of informal consultation, team composition (mixing experienced with inexperienced), and clinical decision aids. The markedly negative view of inexperienced residents suggests a higher risk for disillusionment, perhaps even moral injury, during future redeployments. Implications for planning are explored.